2008
DOI: 10.1530/rep-08-0069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kaempferia parviflora extracts on reproductive parameters and spermatic blood flow in male rats

Abstract: Krachaidum (KD, Kaempferia parviflora Wall. Ex. Baker), a native plant of Southeast Asia, is traditionally used to enhance male sexual function. However, only few scientific data in support of this anecdote have been reported. The present study investigated the effects offeeding three different extracts of KD (alcohol, hexane, and water extracts) for 3-5 weeks on the reproductive organs, the aphrodisiac activity, fertility, sperm motility, and blood flow to the testis of male rats. Sexual performances (mount l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 29 publications
2
45
0
Order By: Relevance
“…For example, Wattanapitayakul et al (2008) have shown that KPE inhibits contractions to phenylephrine in the rat aorta. A previous study by Chaturapanich et al (2008) has demonstrated that blood fl ow to the testes is increased after long-term treatment of KPE in male rats. Recently, a study by our group has shown that KPE induces vasorelaxation in the rat isolated aorta (Tep-areenan et al, 2010).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…For example, Wattanapitayakul et al (2008) have shown that KPE inhibits contractions to phenylephrine in the rat aorta. A previous study by Chaturapanich et al (2008) has demonstrated that blood fl ow to the testes is increased after long-term treatment of KPE in male rats. Recently, a study by our group has shown that KPE induces vasorelaxation in the rat isolated aorta (Tep-areenan et al, 2010).…”
Section: Discussionmentioning
confidence: 91%
“…In addition, relaxant responses to DMF are largely due to opening of K + channels and inhibition of extracellular Ca 2+ infl ux. Previous studies have reported the vasorelaxant effects of KPE (Wattanapitayakul et al, 2008;Chaturapanich et al, 2008). For example, Wattanapitayakul et al (2008) have shown that KPE inhibits contractions to phenylephrine in the rat aorta.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its rhizome has been used in folk medicine reportedly for health promotion and stimulation. Several pharmacological responses to KP and its components have been claimed, including aphrodisiac (Sudwan et al, 2006;Wattanapitayakul et al, 2007;Chaturapanich et al, 2008;Wattanathorn et al, 2012), antipeptic ulcer (Rujjanawate et al, 2005), anti-inflammatory Sae-wong et al, 2009;Nakao et al, 2011), antiallergenic , antimutagenic (Azuma et al, 2011), antidepressive (Wattanathorn et al, 2007), antimicrobial (Yenjai et al, 2004Kummee et al, 2008), anticholinesterase (Sawasdee et al, 2009), anticancer (Wen et al, 2005;Banjerdpongchai et al, 2008;Leardkamolkarn et al, 2009;Wudtiwai et al, 2011), cardioprotective (Tep-areenan et al, 2010;Malakul et al, 2011a,b), and antiobesity activity (Akase et al, 2011). In addition, inhibition of P-glycoprotein function and multidrug resistance-associated protein by KP have been demonstrated (Patanasethanont et al, 2007a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Krachaidum has been used as a traditional herbal medicine for the treatment of various illnesses, including gastrointestinal disorders, gout, allergy, and apthous ulcer [Saralamp et al, 1996]. Interestingly, krachaidum also has been used as an aphrodisiac herb, because it enhances male sexual function [Chaturapanich et al, 2008]. Recently, biological activities of krachaidum have been studied and polymethoxyflavones (PMFs) were identified as major compounds by Yenjai et al [2004].…”
mentioning
confidence: 99%